Successfully Navigating the Merger of Three Academic Departments into One - Amy B Harkins PhD; Mardell A Wilson EdD (Academic Chairpersons Conference Proceedings, 2019)
The presentation will focus on the reasons that lead to the merger, the actual process of the merger, various change-management strategies, and the lessons learned. Participants will be encouraged to actively engage with questions and discussions throughout the presentation.
Keywords: Academic challenges; departmental culture; mergers; academic leadership; change management; reorganization